Implementation of International Nuclear Counterterrorism Legal Instruments: The Case for Nuclear Forensics - Jerry S. Davydov (International Journal of Nuclear Security, 2025)
In the past three decades, the international community and national governments have made great strides in addressing the threat posed by non-state actors or terrorist groups acquiring and maliciously using nuclear or other radioactive material. Although many argue that accomplishments have adequately addressed nuclear security threats, major gaps still remain within the global nuclear security system. Predetonation nuclear forensic science, commonly referred to as nuclear forensics, like all forms of forensic science, supports the implementation of national laws and statutes and international legal instruments through investigative science. Nuclear forensics provides law enforcement and nuclear security investigators with a technical basis for answering key questions related to the seizure of nuclear and other radioactive material out of regulatory control. The question addressed in this paper involves how national legal frameworks related to nuclear or other radioactive material out of regulatory control in line with key international nuclear counterterrorism legal instruments can benefit from the implementation of nuclear forensics.
Keywords: Nuclear forensics; Nuclear law; Nuclear counter-terrorism; CPPNM; CPPNM/A; ICSANT; UNSCR 1540